Studi Komparasi Hukum Perlindungan Konsumen dalam Transaksi Jual Beli Online antara Indonesia dengan Malaysia - Christiana, Christiana; Fitri, Winda; Silviani, Ninne Zahara (Postgraduate Program in Law, Pattimura University, 2024)
Introduction: Legal protection of consumer in online buying and selling transactions is an urgency in today’s developments. Statistical data from National Consumer Protection Agency shows that from the beginning of 2024 until now receiving complaints from consumers is dominant of e-commerce field.Purposes of the Research: The purpose of this article is to examine the differences in consumer protection laws in online buying and selling transactions in Indonesia and Malaysia which are expected to be applied in Indonesia.Methods of the Research: The research method used in this research is normative legal research with a statutory approach and comparative approach with literature study.Results Originality of the Research: The results show that both Indonesia and Malaysia protect online buying and selling transactions. In dispute resolution, Malaysia’s TTPM and Indonesia’s BPSK provide final and binding decisions with an appeal mechanism to the courts. However, Indonesia lacks specific regulations for e-commerce, while Malaysia has comprehensive regulations and strong law enforcement. In Indonesia, the existing regulations and their enforcement face challenges, particularly in the context of e-commerce. The current UUPK is seen as ineffective, and it is hoped that the Indonesia government will amend it soon to strengthen the law enforcement and improve its effectiveness.